Peranan Pemuda dalam Partisipasi Menyukseskan Kegiatan Yang Terafiliasi Partai Politik - Suwarji Suwarji (Sinar Dunia: Jurnal Riset Sosial Humaniora dan Ilmu Pendidikan, 2022)
The role of youth as the first generation of the Indonesian nation can be seen from the role of youth as agents of change. This study aims to provide a description of the role of youth in participating in the success of activities affiliated with political parties. The research approach used is descriptive with the type of research mixed method. The quantitative approach method uses the Kolmogorov-Smirnov method of hypothesis testing and analysis of variance through the two-way Friedman level. This study concludes first that the responses of the respondents, both youth and women, to activities affiliated with political parties are no different or the same. This means that activities affiliated with political parties are considered equally good by young people and women. Second, youths have significant differences in preferences for the four types of activities affiliated with political parties. In this condition, the youth as respondents considered that the four activities affiliated with political parties have different levels of advantages and disadvantages so that their preferences for the four are also different. There is a certain tendency in choosing activities affiliated with political parties.